CD8+ T cells from SIV elite controller macaques recognize Mamu-B*08-bound epitopes and select for widespread viral variation. - John T Loffredo; Thomas C Friedrich; Enrique J León; Jason J Stephany; Denise S Rodrigues; Sean P Spencer; Alex T Bean; Dominic R Beal; Benjamin J Burwitz; Richard A Rudersdorf; Lyle T Wallace; Shari M Piaskowski; et al. (PLoS ONE)
Background It is generally accepted that CD8+ T cell responses play an important role in control of immunodeficiency virus replication. The association of HLA-B27 and -B57 with control of viremia supports this conclusion. However, specific correlates of viral control in individuals expressing these alleles have been difficult to define. We recently reported that transient in vivo CD8+ cell depletion in simian immunodeficiency virus (SIV)-infected elite controller (EC) macaques resulted in a brief period of viral recrudescence. SIV replication was rapidly controlled with the reappearance of CD8+ cells, implicating that these cells actively suppress viral replication in ECs. Methods and findings Here we show that three ECs in that study made at least seven robust CD8+ T cell responses directed against novel epitopes in Vif, Rev, and Nef restricted by the MHC class I molecule Mamu-B*08. Two of these Mamu-B*08-positive animals subsequently lost control of SIV replication. Their breakthrough virus harbored substitutions in multiple Mamu-B*08-restricted epitopes. Indeed, we found evidence for selection pressure mediated by Mamu-B*08-restricted CD8+ T cells in all of the newly identified epitopes in a cohort of chronically infected macaques. Conclusions Together, our data suggest that Mamu-B*08-restricted CD8+ T cell responses effectively control replication of pathogenic SIV(mac)239. All seven regions encoding Mamu-B*08-restricted CD8+ T cell epitopes also exhibit amino acid replacements typically seen only in the presence of Mamu-B*08, suggesting that the variation we observe is indeed selected by CD8+ T cell responses. SIV(mac)239 infection of Indian rhesus macaques expressing Mamu-B*08 may therefore provide an animal model for understanding CD8+ T cell-mediated control of HIV replication in humans.